(untitled) (TẠP CHÍ Y DƯỢC THÁI BÌNH, 2024)
Objective: This study aims to identify the clinical features and factors associated with atopic dermatitis (AD) at Thai Binh University Hospital, as well as to analyze the relationship between disease severity and quality of life of patients. Method: A cross-sectional study was conducted with 225 patients diagnosed with atopic dermatitis at Thai Binh University Hospital in 2022. Patients were surveyed on clinical factors, disease severity using the SCORAD index, and quality of life using the DLQI scale. Data analysis was performed using descriptive statistics, correlation, and linear regression methods. Results: The results showed a strong correlation between stress levels and both SCORAD (r = 0.56) and DLQI (r = 0.35) scores. Furthermore, factors such as allergic history and stress levels had a significant impact on disease severity and quality of life (p < 0.01). Linear regression analysis indicated that allergic history and stress levels were the most significant factors influencing disease severity and quality of life (β = 0.42 and β = 0.25, p < 0.01). Conclusion: Factors such as allergic history and stress levels have a significant impact on the severity and quality of life of patients with atopic dermatitis. Managing stress and controlling allergic factors may improve patients’ quality of life and help manage disease severity.